Esio Trot - Dahl, Roald; Blake, Quentin (London : Puffin Books, 2013)
Shy Mr. Hoppy devises a plan to win the heart of his true love by teaching her a spell to make her tortoise grow bigger.
4.9
3-6.
3-6
Keywords: Magic -- Juvenile fiction; Size -- Juvenile fiction; Turtles -- Juvenile fiction; Magic -- Fiction; Size -- Fiction; Turtles -- Fiction; Magic -- Fiction; Size -- Fiction; Turtles -- Fiction